Effect of fermented spent instant coffee grounds on milk productivity and blood profiles of lactating dairy cows - Choi, Yongjun (Asian-Australasian journal of animal sciences, 2019)
OBJECTIVE: This study was conducted to evaluate the fermentation characteristics under low mesophilic temperature of spent instant coffee ground (SICG) and to estimate the effect of fermented SICG (FSICG) as alternative feed ingredient on milk productivity of dairy cows